2017
DOI: 10.1002/pros.23431
|View full text |Cite
|
Sign up to set email alerts
|

High‐Level Glyoxalase 1 (GLO1) expression is linked to poor prognosis in prostate cancer

Abstract: GLO1 upregulation is linked to aggressive prostate cancers characterized by ERG fusion and PTEN deletion. The strong and independent prognostic value makes it a promising candidate for routine diagnostic applications either alone or in combination with other markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…GLO1 was found to be upregulated in pancreatic cancerous (Wang et al, 2012), hepatocellular carcinoma (Zhang et al, 2014), lung cancer (Santarius et al, 2010) and gastric cancer (Wang & Lin, 2011). Abnormal expression of GLO1 in cancers is linked to poor prognosis, malignant tumor phenotype and cancer metastasis (Burdelski et al, 2017), and we found that GLO1 expression was upregulated in LUAD. The clinical data exhibited that FAM201A expression was negatively correlated with miR‐7515 expression, and positively correlated with GLO1 expression.…”
Section: Discussionsupporting
confidence: 53%
“…GLO1 was found to be upregulated in pancreatic cancerous (Wang et al, 2012), hepatocellular carcinoma (Zhang et al, 2014), lung cancer (Santarius et al, 2010) and gastric cancer (Wang & Lin, 2011). Abnormal expression of GLO1 in cancers is linked to poor prognosis, malignant tumor phenotype and cancer metastasis (Burdelski et al, 2017), and we found that GLO1 expression was upregulated in LUAD. The clinical data exhibited that FAM201A expression was negatively correlated with miR‐7515 expression, and positively correlated with GLO1 expression.…”
Section: Discussionsupporting
confidence: 53%
“…GLO1 upregulation has been described in the context of metabolic and inflammatory stress in vitro and in vivo [ 17 , 18 , 19 , 20 ], serving as a cellular mechanism to detoxify high levels of MG, particularly in cancer, where high glycolytic rates as a result of the Warburg effect are observed. Previous reports have shown upregulation of GLO1 in various cancers including melanoma [ 21 ], breast cancer [ 22 , 23 , 24 ], prostate cancer [ 25 , 26 ], gastric cancer [ 27 , 28 ], pancreatic cancer [ 29 ] and renal carcinoma (clear cell carcinoma) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies have reported GLO1 upregulation in PCa patient tissue samples detecting a wide range of staining intensity [ 25 , 26 ]. GLO1 displayed a strong association with Gleason grade, pathological tumor stage, and early biochemical recurrence (BCR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells are characterized by their elevated metabolic rate, resulting in the escalation of the sequential toxic metabolites, including MG and SLG [9,10]. Tumor cells counter that by intensifying the activity of both Glo-I and Glo-II [8,11,12,13] as reported in multiple cancers such as stomach cancer [14,15], murine fibrosarcoma [16], pancreatic cancerous tissues [17], colon cancer [18], prostate cancers [19], and endometrial cancer cells [20]. Inhibition of Glo-I enzyme in cancer cells will lead to the accumulation of MG, leading to cytotoxicity and, subsequently, self-destruction of the cancer cells [7,21,22].…”
Section: Introductionmentioning
confidence: 99%